Thermally induced neuronal plasticity in the hypothalamus mediates heat tolerance - Ambroziak, Wojciech; Nencini, Sara; Pohle, Jörg; Žuža, Kristina; Pino, Gabriela; Lundh, Sofia; Araujo Sousa, Carolina; Götz, Larissa; Schrenk-Siemens, Katrin; Manoj, Gokul; Gutierrez-Herrera, Mildred A.; Acuna Goycolea, Claudio; et al. (Nature neuroscience, 2025)
Heat acclimation is an adaptive process that improves physiological performance and supports survival in the face of increasing environmental temperatures, but the underlying mechanisms are not well understood. Here we identified a discrete group of neurons in the mouse hypothalamic preoptic area (POA) that rheostatically increase their activity over the course of heat acclimation, a property required for mice to become heat tolerant. In non-acclimated mice, peripheral thermoafferent pathways via the parabrachial nucleus activate POA neurons and mediate acute heat-defense mechanisms. However, long-term heat exposure promotes the POA neurons to gain intrinsically warm-sensitive activity, independent of thermoafferent parabrachial input. This newly gained cell-autonomous warm sensitivity is required to recruit peripheral heat tolerance mechanisms in acclimated animals. This pacemaker-like, warm-sensitive activity is driven by a combination of increased sodium leak current and enhanced utilization of the NaV1.3 ion channel. We propose that this salient neuronal plasticity mechanism adaptively drives acclimation to promote heat tolerance.
Online veröffentlicht: 09. Dezember 2024
Gesehen am 06.05.2025